Safety, pharmacokinetics, biomarker response and efficacy of E6742: a dual antagonist of Toll-like receptors 7 and 8, in a first in patient, randomised, double-blind, phase I/II study in systemic lupus erythematosus - Tomonori Ishii; Yoshiya Tanaka; Atsushi Kumanogoh; Tatsuya Atsumi; Shizuo Akira; Fumitoshi Tago; Mari Aoki; Shintaro Yamamuro (RMD Open)
Objectives To evaluate the safety, tolerability, pharmacokinetics (PK), biomarker response and efficacy of E6742 in a phase I/II study in patients with systemic lupus erythematosus (SLE).Methods Two sequential cohorts of patients with SLE were enrolled and randomised to 12 weeks of two times per day treatment with E6742 (100 or 200 mg; n=8 or 9) or placebo (n=9). The primary endpoint was safety, the secondary endpoints were PK and interferon gene signature (IGS), and the exploratory endpoints were efficacy and biomarker.Results The proportion of patients with any treatment-emergent adverse events (TEAEs) was 58.8% in the E6742 group (37.5% (3/8 patients) for 100 mg; 77.8% (7/9 patients) for 200 mg) and 66.7% (6/9 patients) in the placebo group. No Common Terminology Criteria for Adverse Events≥Grade 3 TEAEs occurred. PK parameters were similar to these in previous phase I studies in healthy adults. The IGS and levels of proinflammatory cytokines after ex-vivo challenge with a Toll-like receptor 7/8 agonist were immediately decreased by E6742 treatment. The response rate of the British Isles Lupus Assessment Group-based Composite Lupus Assessment at week 12 was 37.5% (3/8 patients) for E6742 100 mg, 57.1% (4/7 patients) for E6742 200 mg and 33.3% (3/9 patients) for placebo group.Conclusions E6742 had a favourable safety profile and was well tolerated, with suppression of IGS responses and preliminary efficacy signals in patients with SLE. These results provide the first clinical evidence to support E6742 in the treatment of SLE, and support larger, longer-term clinical trials.Trial registration number NCT05278663.